2016
DOI: 10.1016/j.eplepsyres.2016.01.009
|View full text |Cite
|
Sign up to set email alerts
|

The sensitivity and significance of lateralized interictal slow activity on magnetoencephalography in focal epilepsy

Abstract: Objective Asymmetric large-amplitude slow activity is sometimes observed on interictal electroencephalography (EEG) in epilepsy. However, few studies have examined slowing during magnetoencephalography (MEG) recordings, which are performed primarily to localize interictal spikes. Also, no prior investigations have compared the sensitivity of MEG to scalp EEG in detecting slow rhythms. Methods We performed a retrospective cohort study of focal epilepsy patients who received MEG followed by surgical resection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Previous studies have shown that dipole modeling of high density EEG and MEG delta activity is related to lesion location on MRI in the majority of patients with lesional epilepsy ( Baayen et al, 2003 ). Asymmetric slowing in MEG was found to reliably lateralize the resected area, although localizing value was limited ( Englot et al, 2016a ; Ishibashi et al, 2002 ). Our observations from MEG-VE and SEEG are in line with these results, and in addition provide localizing information.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that dipole modeling of high density EEG and MEG delta activity is related to lesion location on MRI in the majority of patients with lesional epilepsy ( Baayen et al, 2003 ). Asymmetric slowing in MEG was found to reliably lateralize the resected area, although localizing value was limited ( Englot et al, 2016a ; Ishibashi et al, 2002 ). Our observations from MEG-VE and SEEG are in line with these results, and in addition provide localizing information.…”
Section: Discussionmentioning
confidence: 99%
“…MEG data more closely reflect neural signals, but source localization is challenging with deep structures . Although scalp EEG is also widely available and noninvasive, connectivity analyses are limited by low spatial resolution and signal degradation by the scalp and skull …”
Section: Connectivity Analysis Modalities and Methodsmentioning
confidence: 99%
“…16 Although scalp EEG is also widely available and noninvasive, connectivity analyses are limited by low spatial resolution and signal degradation by the scalp and skull. 17 Analysis techniques in functional connectivity studies are often categorized as either model based or data driven. Table 2 summarizes some of the most common modelbased and data-driven methods utilized.…”
Section: Key Pointsmentioning
confidence: 99%
“…Thus, method that can analyze the effects of different frequency bands, especially the frequency band in which epileptiform discharges, was generated. Studies have shown that asymmetric and slow activity of the delta band (1-4 Hz) can reliably lateralize to the epileptogenic hemisphere [14,[60][61][62]. Indeed, significant differences in delta band activity were found between TLE patients and controls in network analyses [31,63,64].…”
Section: Complexitymentioning
confidence: 99%
“…During the last decade, MEG has become increasingly available as a noninvasive, reliable, fast, and patient-friendly technique for recording brain activity [11][12][13][14]. MEG has been widely applied for studying epilepsy disorders, particularly the localization of pathological brain activity or lesions in candidates for epilepsy surgery [15][16][17].…”
Section: Introductionmentioning
confidence: 99%